Tau expression and phosphorylation in enteroendocrine cells - Chapelet, Guillaume; Béguin, Nora; Castellano, Blandine; Grit, Isabelle; de Coppet, Pierre; Oullier, Thibauld; Neunlist, Michel; Blottière, Hervé; Rolli-Derkinderen, Malvyne; Le Dréan, Gwenola; Derkinderen, Pascal (Frontiers in Neuroscience, 2023)
Background and objective There is mounting evidence to suggest that the gut-brain axis is involved in the development of Parkinson’s disease (PD). In this regard, the enteroendocrine cells (EEC), which faces the gut lumen and are connected with both enteric neurons and glial cells have received growing attention. The recent observation showing that these cells express alpha-synuclein, a presynaptic neuronal protein genetically and neuropathologically linked to PD came to reinforce the assumption that EEC might be a key component of the neural circuit between the gut lumen and the brain for the bottom-up propagation of PD pathology. Besides alpha-synuclein, tau is another key protein involved in neurodegeneration and converging evidences indicate that there is an interplay between these two proteins at both molecular and pathological levels. There are no existing studies on tau in EEC and therefore we set out to examine the isoform profile and phosphorylation state of tau in these cells. Methods Surgical specimens of human colon from control subjects were analyzed by immunohistochemistry using a panel of anti-tau antibodies together with chromogranin A and Glucagon-like peptide-1 (two EEC markers) antibodies. To investigate tau expression further, two EEC lines, namely GLUTag and NCI-H716 were analyzed by Western blot with pan-tau and tau isoform specific antibodies and by RT-PCR. Lambda phosphatase treatment was used to study tau phosphorylation in both cell lines. Eventually, GLUTag were treated with propionate and butyrate, two short chain fatty acids known to sense EEC, and analyzed at different time points by Western blot with an antibody specific for tau phosphorylated at Thr205. Results We found that tau is expressed and phosphorylated in EEC in adult human colon and that both EEC lines mainly express two tau isoforms that are phosphorylated under basal condition. Both propionate and butyrate regulated tau phosphorylation state by decreasing its phosphorylation at Thr205. Conclusion and inference Our study is the first to characterize tau in human EEC and in EEC lines. As a whole, our findings provide a basis to unravel the functions of tau in EEC and to further investigate the possibility of pathological changes in tauopathies and synucleinopathies.